Moral value of smart hafiz toys for children worship series with the title â€œdonâ€Ÿt lieâ€ - Salamah Salamah; Idawati Idawati; Bastian Sugandi (PROCEEDING UMSURABAYA, 2020)
Abstract This research was conducted to determine the moral values contained in SmartHafiz. The are several components contained in Smart Hafizincluding pre schoolanimation, educational animation, Diva the series, movies, worship series, ahlakpraiseworthy, 30 juz, asmaulhusna, little child, 44 sing a song, and your body. Smart Hafiz series of worship sessions "Do not Like to Lie" had a bad value in the show for children. Therefore, this study was conducted to obtain these data with the aim that parents always accompany their children when viewing shows on Smart Hafiz. This research was focused only on the worship series, using qualitative descriptive methods. This research method tended to analyze the data that had been presented. With the theoretical foundation used as a guide for the focus of research in accordance with existing data. The results of this study were explained based on the story titled â€•Don't Like to Lie". Categories of moral values contained in the story are: Honesty, authentic, willingness to be responsible, independence, courage, humility, reality and critical. Based on the category of moral values, it was dominated by reality and critical values, while moral values were the least value of willingness to be responsible, independence, and humility. Smart Hafiz worship series session with the title "Do not Like to Lie" reflected the real attitude of life both towards fellow human beings and the Creator.